2016
DOI: 10.3847/0004-637x/831/1/92
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency Photo-Polarimetric Webt Observation Campaign on the Blazar S5 0716+714: Source Microvariability and Search for Characteristic Timescales*

Abstract: Here we report on the results of the WEBT photo-polarimetric campaign targeting the blazar S5 0716+71, organized in March 2014 to monitor the source simultaneously in BVRI and near IR filters. The campaign resulted in an unprecedented dataset spanning ∼ 110 h of nearly continuous, multi-band observations, including two sets of densely sampled polarimetric data mainly in R filter. During the campaign, the source displayed pronounced variability with peak-to-peak variations of about 30% and "bluer-when-brighter"… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 89 publications
9
55
0
Order By: Relevance
“…Intra-day variabilities (IDVs) have been studied by many authors (Poon et al 2009;Liu et al 2012;Gupta et al 2012;Bhatta et al 2013;Man et al 2016;Lee et al 2016, etc.). Gupta et al (2009) obtained timescales of 25 min; Rani et al (2010) obtained timescales of 15 min; Man et al (2016) obtained timescales of 17.6 min; and Bhatta et al (2016) displayed the variability based on the A&A 605, A43 (2017) peak-to-peak variations of 30% and "bluer-when-brighter" spectral evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Intra-day variabilities (IDVs) have been studied by many authors (Poon et al 2009;Liu et al 2012;Gupta et al 2012;Bhatta et al 2013;Man et al 2016;Lee et al 2016, etc.). Gupta et al (2009) obtained timescales of 25 min; Rani et al (2010) obtained timescales of 15 min; Man et al (2016) obtained timescales of 17.6 min; and Bhatta et al (2016) displayed the variability based on the A&A 605, A43 (2017) peak-to-peak variations of 30% and "bluer-when-brighter" spectral evolution.…”
Section: Introductionmentioning
confidence: 99%
“…In such a scenario, the electrons with lower energies E e ∝ 1/ √ B in an amplified magnetic field intensity B would produce enhanced synchrotron emission at a given observed frequency, representing, in the present context, microflares with bluer color (flatter spectra). On the other hand, the 6 h plateau seen both in the 2014 and the 2003 campaigns can be used to place a constraint on the upper limit for the S5 0716+714 black hole mass, which can be estimated as M 4 × 10 9 M for a maximally spinning supermassive black hole (SMBH) (r isco r g ), and M 3 × 10 8 M for very low spin values (r isco 6 r g ) (For details on the calculations, see [18]). The study of the polarization properties revealed that any coherent correlation between flux and polarization properties (e.g., PD leading the total flux changes, hysteresis in the PD-F plane) might depend on the particular configuration of the orientation of ambient magnetic field in relation to the direction of the radio core of the jet.…”
Section: Discussionmentioning
confidence: 99%
“…The data gathered during the period are shown in Figure 2; the vertical lines on Figure 2 mark the microflares we considered for the detailed analysis. The list of the participating observatories and other details on the observational campaign are described in [18]. As explained earlier, one of the primary motivations of these extended campaigns was to probe the temporal behavior of the source in the rather-unexplored time domain spanning from more than 12 h up to few days, without major interruption in between.…”
Section: Multi-site Photo-polarimetric Campaign On S5 0716+714 In 201mentioning
confidence: 99%
See 1 more Smart Citation
“…Setup takes place during the day, the telescope performs all observations at night without operator assistance, and shuts down automatically at dawn. Over 30 students have been trained on it, while producing or contributing to approximately one refereed monitoring paper per year (e.g., [4][5][6][7][8][9][10]). …”
Section: Introductionmentioning
confidence: 99%